The influence of corporate governance on dividend pay out ratio in non-cycal sector companies listed on the indonesian stock exchange - Pardhana, Feza; Rahim, Rida; Adrianto, Fajri (Institute of Computer Science (IOCS), 2024)
This research aims to analyze the influence of corporate governance on the dividend payout ratio in companies included in the non-cyclical sector group listed on the Indonesia Stock Exchange. Corporate governance is measured by variables, the research consists of independent variables, namely busy directors, institutional ownership, independent commissioner, audit committee, managerial ownership and the dependent variable dividend payout ratio and the control variables, leverage, company size and company age are also used. In this research, panel data regression analysis is used. The sample in this research consisted of 33 companies consisting of the 2018-2012 period. The research results show that busy directors have a significant negative effect on dividend policy, institutional ownership has no effect on dividend policy, independent commissioners have no effect on dividend policy, audit committees have no effect on dividend policy, managerial ownership has no effect on dividend policy. The control variable leverage has a significant negative effect, company size has a significant positive effect, company age has no effect on dividend policy